The strange love of Martha Ivers - Milestone, Lewis, 1895-1980; Wallis, Hal B., 1899-1986; Rossen, Robert, 1908-1966; Stanwyck, Barbara, 1907-1990; Paramount Pictures Corporation (1914-1927) ([Hollywood] : Paramount Pictures Corporation, 1946)
Martha Smith Yvers (Barbara Stanwyck) is a young woman who tries to escape the clutches of her possessive aunt with her friend Sam Masterson (Van Heflin), but fails time and time again. During a last attempt, in a fit of anger and frustration, she pushes her aunt down the stairs, causing her death, which is witnessed by Sam and Walter (Kira Douglas), the son of the guardian of her. She will say that her aunt was the victim of a murderer. Years later, a fortuitous car accident will bring Sam to a stop in Iverstown, where he will meet up with Walter, a brilliant district attorney and his now wife, Martha, a wealthy industrialist. The couple will think that Sam is back to blackmail them, leading to a continuing series of misunderstandings, plots and conspiracies. --
Barbara Stanwyck, Van Heflin, Lizabeth Scott, Kirk Douglas, Judith Anderson, Roman Bohnen, Darryl Hickman, Janis Wilson, Ann Doran.
Director of photography, Victor Milner.
In English or Spanish.
Best Original Story - Oscars
Online resource; title from opening/closing credits (Digitalia Film Library, viewed February 4, 2022)
Keywords: Married people -- Drama; Triangles (Interpersonal relations) -- Drama; Murder -- Drama; Motion pictures; Film posters; Streaming video